Analysis of the Impact of Digital Educational Media on Students Knowledge and Attitudes towards Mangrove Conservation in Pari Island - Ramadian, Naufal; Rohim, Syaiful; Alimudin, M. (Lembaga KITA, 2025)
This study aims to evaluate the impact of digital educational media on students’ knowledge and attitudes toward mangrove conservation on Pari Island. As environmental issues gain increasing urgency, the adoption of digital learning methods emerges as a strategic approach to enhance environmental literacy among younger generations. Employing a quantitative methodology, this research involved 92 students from Universitas Muhammadiyah Bogor Raya (UMBARA) who participated in a digital-based environmental education program. Data were collected using validated questionnaires and analyzed through descriptive statistics and simple linear regression with the assistance of SPSS software. The findings reveal that digital educational media significantly and positively influence the improvement of students’ knowledge and attitudes. Post-intervention, the average knowledge score reached 76.4, while the attitude score attained 78.2 on a 100-point scale. Regression analysis further demonstrates a significant effect of digital media on knowledge (β = 0.621; p < 0.05) and attitudes (β = 0.587; p < 0.05). These results suggest that digital learning content effectively fosters environmental awareness and pro-environmental behavior. The study concludes that digital education serves as a valuable tool for instilling conservation values, particularly when applied within local settings such as Pari Island. Furthermore, the outcomes support the incorporation of digital environmental education into higher education curricula and community service programs to cultivate ecological responsibility and engagement among students.